2020
DOI: 10.1589/jpts.32.260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic exercise utilizing PNF patterns on the balance of healthy adults

Abstract: The purpose of this study is to examine the effects of dynamic exercise utilizing the proprioceptive neuromuscular facilitation patterns accompanied by the abdomen drawing-in on balance of healthy adults. [Participants and Methods] The total number of participants was 30, and 15 were randomly placed in the training group (TG) and 15 in the control group (CG). The participants in the TG have conducted the 3 sets to 5 sets of dynamic exercise utilizing the proprioceptive neuromuscular facilitation patterns per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, Gong [25] also reported that balance ability improved in the training group after six weeks of PNF patterns exercise.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, Gong [25] also reported that balance ability improved in the training group after six weeks of PNF patterns exercise.…”
Section: Discussionmentioning
confidence: 90%
“…The experimental group performed dynamic exercise using the PNF patterns for 6 weeks, and the experimental group showed an increase in the thickness of the deep abdominal muscles that contribute to trunk stabilization. In addition, Gong [ 25 ] also reported that balance ability improved in the training group after six weeks of PNF patterns exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different outcomes also emerge when considering the effects of PNF on balance. The majority of the investigations carried out on healthy subjects, observe increases in both static and dynamic balance parameters [ 78 80 ]. These are particularly evident pertaining to dynamic balance in the medio-lateral direction [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proprioceptive neural facilitation (PNF) is an elemental physiotherapeutic strategy (Gong, 2020) that is associated with specific movement patterns in diagonal and spiral directions (Areas et al, 2013;Slupska et al, 2019). Physiotherapists frequently use this technique to increase muscle intensity, proprioception, active range of motion, and motor control (Hindle et al, 2012;Sayaca et al, 2020).…”
Section: The Exercise As a Viable Rehabilitation Optionmentioning
confidence: 99%